Improved Version of the Tactile/Force Sensor Based on Optoelectronic Technology. (2016) - Cirillo, A.; Cirillo, P.; De Maria, G.; Natale, C.; Pirozzi, S.
Abstract: The aim of this paper is to introduce an improved version of the tactile sensor already presented by the authors. The tactile sensor provides an accurate estimation of the contact wrench and a tactile map related to the contact geometries. With respect to the old sensor version, the improvements concern: the spatial resolution, increased by exploiting 25 couples of infrared LED and photodetector; the full-scale, become four times higher; the new digitalization technique, introduced in order to reduce the overall wire number and power consumption.